2001
DOI: 10.1159/000050997
|View full text |Cite
|
Sign up to set email alerts
|

Perineal Ectopic Testis: A Rare Cause of Empty Scrotum

Abstract: Perineal ectopic testis is a rare congenital anomaly and remains a urologic curiosity. We report the course of 2 recurrent cases after hormonal therapy and a third case associated with inguinal hernia. During the surgical exploration, the gubernaculum testis was found fixed to the perineum. The testes were placed in the scrotum. The evaluation of differential diagnosis of empty scrotum is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Site of the ectopic testis is probably decided by the strength of the tail of gubernaculum. Normally scrotal tail is the strongest hence testis descends down into the scrotum [6,7]. In the case under review, Ultrasound scan confirmed the swelling to be a testis in the ectopic location.…”
Section: Discussionmentioning
confidence: 93%
“…Site of the ectopic testis is probably decided by the strength of the tail of gubernaculum. Normally scrotal tail is the strongest hence testis descends down into the scrotum [6,7]. In the case under review, Ultrasound scan confirmed the swelling to be a testis in the ectopic location.…”
Section: Discussionmentioning
confidence: 93%
“…Clinical findings of ectopic testis (Soomro and Mughal, 2008) have supported the theory of testis descent following these tails. Ectopic locations have represented up to 10% of undescended testes (Davenport, 1996;Nounla et al, 2001) and these positions coincide with the gubernacular attachments. Transverse testicular ectopia (Fernández Jiménez et al, 2000;Marín Mata et al, 2005;Shamsuddin et al, 2007;Thambidorai and Khaleed, 2007), with both gubernacula in the same inguinal canal, could be caused by a minor displacement in early ligament insertion on the pubic bone, which should determine the inclusion within the contralateral wall.…”
Section: Discussionmentioning
confidence: 95%
“…Orchiopexy is a surgical procedure that is commonly used to move an undescended testis into the scrotum. It is typically performed on infants and young boys aged 6 to 15 months [9].…”
Section: Discussionmentioning
confidence: 99%